Determinants of Consumer Buying Interest - Ramadhani, Adellya Sagita; Hayati, Isra (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2023)
The objective of this study is to evaluate the influence of pricing, product quality, and innovation on consumer purchasing intention within the specific setting of the Syar'I Collection & Parfum Business in Riau. The major data utilised in this study is derived from questionnaire replies. The data were acquired through documentation approaches employing structured questionnaires. This study centres on individuals who engage with Syar'I Collection and Perfume Enterprises. The researchers employed incidental sampling methods to choose participants. The research findings indicate a significant impact of pricing on customer purchasing behaviour within the Syar'I Collection and Perfume industry. This suggests that the implementation of price reductions by Syar'I Collection and Parfum Business companies is likely to enhance consumer inclination towards product purchases. Furthermore, this study elucidates a robust correlation between the quality of products and the level of consumer purchasing interest within the Syar'I Collection and Perfume industry. The findings indicate a positive relationship between the enhancement of product quality by Syar'I Collection and Parfum Business companies and the growing inclination of consumers to make investments in these products. This study provides empirical evidence that highlights the significant influence of product innovation on customer purchasing behaviour within the Syar'I Collection and Perfume Business industry. This statement elucidates that the heightened focus on inventive product offerings by Syar'I Collection and Parfum enterprises has resulted in a surge in consumer enthusiasm in procuring these products.